The Show in Education: TikTok Teachers’ Influencers - Azzari, Eliane Fernandes; Mayer, Lucas Falvo (Cadernos de Educação Tecnologia e Sociedade, 2022)
This paper proposes a brief discussion of some excerpts of TIkTok public video-posts retrieved from the profile of two popular teachers. It is discussed that such teachers assume the role of digital influencers whilst adopting the practice of video production and sharing, whenever they focus on educational topics or not. Digital ethnography is adopted as a methodology, and the researchers trust on screenshot tools as a method to select and capture imagens from the videos that are hereby represented by figures. The discussion finds support in the Literacies studies to broach issues related to the place of education and teaching in the contemporaneity. It also searches for support in other studies, related to concepts of culture, cultural industry, mass communication, and the public-show society to build up a qualitative and interpretative reading of the data presented.